2013
DOI: 10.1007/s00701-013-1679-z
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation management of myocardial infarction after deep brain stimulation: a comparison of two cases

Abstract: Deep brain stimulation (DBS) is an established treatment of various diseases, particularly used for idiopathic Parkinson's disease. Frequently, DBS patients are multimorbid and managing them may be challenging, since postoperative complications can become more likely with age. In this article, we present two cases of myocardial infarction after DBS with different therapeutic strategies. Case 1 was anticoagulated with a heparin infusion with a target partial thromboplastine time (PTT) between 50 and 60 s after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Another unique aspect is the fact that our patient was on oral anticoagulation before and after chronic DBS. Usually, oral anticoagulation has been considered a contraindication for DBS, and there is little information in its safety profile . Our report demonstrates that DBS can be considered in an individual patient even with long‐term oral anticoagulation.…”
Section: Discussionmentioning
confidence: 86%
“…Another unique aspect is the fact that our patient was on oral anticoagulation before and after chronic DBS. Usually, oral anticoagulation has been considered a contraindication for DBS, and there is little information in its safety profile . Our report demonstrates that DBS can be considered in an individual patient even with long‐term oral anticoagulation.…”
Section: Discussionmentioning
confidence: 86%
“…With respect to patients receiving therapeutic anti-coagulation after DBS, a duo of cases reported by Polanski et al [12] show mixed results. The 2 patients in their case report had undergone DBS yet suffered from a myocardial infarction post-operatively, requiring therapeutic anti-coagulation.…”
Section: Discussionmentioning
confidence: 98%
“…Another study showed that postoperative prophylaxis with or without subcutaneous heparin for venous thromboembolism did not increase the risk for intracranial hemorrhage significantly [ 5 ]. More detailed analysis of the handling of chronic anticoagulation treatment in patients undergoing DBS or with existing DBS systems has been provided mainly in the form of case report or small case series [ 4 , 25 , 31 , 33 , 39 ]. We have reported previously on a patient who received bilateral pallidal DBS for severe chorea due to antiphospholipid antibody syndrome with a need for chronic phenprocoumon treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The question, however, arises whether an established therapy such as DBS can be denied to these groups of patients. While many neurosurgeons worldwide perform DBS in patients with chronic antiplatelet or anticoagulation treatment, there is very limited published data addressing this problem [ 4 , 25 , 31 , 33 , 36 ]. Furthermore, there are different drugs for antiplatelet or anticoagulation treatment, each with distinctive mechanisms and duration of action.…”
Section: Introductionmentioning
confidence: 99%